2012
DOI: 10.1021/jp2107473
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility As an Indicator of Feasibility of Zeolite Frameworks

Abstract: The online database at contains over two million unique hypothetical zeolite structures. By a simple flexibility calculation, we have been able to identify a subset of 5824 flexible structures that exhibit characteristics for synthetic feasibility as zeolites. 78 out of 97 officially approved zeolite framework types that occur in the database are included in this flexible subset, including many that have been synthesized only in mixed and nonsilicate compositions. This suggests that framework flexibility (a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 35 publications
2
49
0
Order By: Relevance
“…Significant advances in this area will be required before it becomes feasible to systematically synthesize and test predicted zeolite structures or defect-free, all-silica variants of already-known zeolite frameworks. Some candidate zeolite structures that are thermodynamically feasible may prove to be synthetically inaccessible due to kinetic barriers in the crystallization process 30 . Recently, Schmidt et al 31 succeeded in using computationally predicted organic structure directing agents to synthesize a particular, specified zeolite; an important step in the synthesis of tailor-made zeolites.…”
Section: Discussionmentioning
confidence: 99%
“…Significant advances in this area will be required before it becomes feasible to systematically synthesize and test predicted zeolite structures or defect-free, all-silica variants of already-known zeolite frameworks. Some candidate zeolite structures that are thermodynamically feasible may prove to be synthetically inaccessible due to kinetic barriers in the crystallization process 30 . Recently, Schmidt et al 31 succeeded in using computationally predicted organic structure directing agents to synthesize a particular, specified zeolite; an important step in the synthesis of tailor-made zeolites.…”
Section: Discussionmentioning
confidence: 99%
“…Also in connection with synthesis methods, a definition of flexibility has been related to zeolite feasibility [17]. Such definition, in simple terms, assess zeolites as either flexible or rigid with respect to possible reorientation of rigid regular SiO 4/2 tetrahedra linked by force-free spherical joints at the vertices, or in other words flexible SiOSi and rigid OSiO and SiO.…”
Section: T Angles In the Feasibility Of Zeolites 297mentioning
confidence: 99%
“…The narrow differences in their relative free energies [15] is a factor against increasing their number, although some new synthesis methods allow to overcome certain energetic barriers by following a less straight synthesis path [13,14]. Assessing zeolite feasibility is a challenging issue and several attempts have been made [16][17][18]. An important result has been reported by Li et al [19] T, and T-O distances (T is a tetrahedral atom), plus one more T-O based condition specifically for aluminosilicate composition.…”
Section: Introductionmentioning
confidence: 99%
“…The only change between IPC-2P and IPC-2 is the completion of the condensation process, so that all (or at least the vast majority) of the silicon atoms end up as Q 4 (Figure 3b). It is interesting to note that the rearrangement process described above leads to scrambling of the oxygen atoms, as can be shown using isotopically-enriched H 2 17 O for the disassembly hydrolysis, as both Si-O-Si and Si-OH oxygens are enriched as shown by 17 O MAS NMR spectra collected at 20.0 T (See supplementary information, Figure 1). This is an important result as it shows the process overall is highly dynamic, with the oxygen atoms from the hydrolysis water being incorporated throughout the material and not just in the interlayer regions as might be expected from a simplistic picture of the reaction.…”
Section: Resultsmentioning
confidence: 81%
“…To explain this we take note of the beautiful work of Sartbaeva, Dawson and coworkers who showed that having some 'flexibility' is an important criterion in determining whether a zeolite can be successfully prepared. 16,17 Figure 5 shows how this concept can be applied to explain why the IPC-6 structure forms. The distance between these two layers is then fixed at that found for IPC-2P as the layers are connected by the rearrangement.…”
Section: Resultsmentioning
confidence: 99%